Hubungan Pengetahuan Ibu Tentang Anemia dengan Kejadian Anemia pada Ibu Hamil di Desa Pulau Sarak Wilayah Kerja UPT Puskesmas Air Tiris Tahun 2022 - Nursila, Nursila; Arvan, Arvan; Hastuty, Milda (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
According to World Health Organization (WHO) data, the prevalence of anemia in pregnant women reaches 41.8% in the world, and ASIA is ranked second in the world after Africa with a prevalence percentage of anemia sufferers in pregnancy of 48.2%. The aim of this research is to determine the relationship between maternal knowledge about anemia and the incidence of anemia in pregnant women in Pulau Sarak Village, Upt Air Tiris Health Center Work Area in 2022. This research design uses quantitative research methods with a cross sectional research design. The research population was all pregnant women in the third trimester recorded in the register of pregnant women for the period November 2022 in Pulau Sarak Village, Air Tiris Health Center Working Area, totaling 36 pregnant women. The sampling technique in this research is Total Sampling. Based on the results of univariate analysis, it was found that of the 36 respondents, the majority of pregnant women's knowledge about anemia was lacking, 22 people (61.1%), and 20 people 56.6% who were not anemic. Based on bivariate analysis with the chi square test, the p value = 0.001 ? (0.05), meaning that there is a relationship between mother's knowledge about anemia and the incidence of anemia in pregnant women in Pulau Sarak Village, Air Tiris Health Center UPT Working Area in 2022. It is hoped that pregnant women to pay more attention to nutritional intake during pregnancy by consuming foods rich in iron and other nutrients that help form red blood cells.